An update on polyphenol disposition via coupled metabolic pathways. (1st February 2019) - Wang, Liping; Sun, Rongjin; Zhang, Qisong; Luo, Qing; Zeng, Sijing; Li, Xiaoyan; Gong, Xia; Li, Yuhuan; Lu, Linlin; Hu, Ming; Liu, Zhongqiu
ABSTRACT: Introduction : Polyphenols, which are widely distributed in plants and the human diets, are known to have numerous biological activities. However, the low bioavailability of polyphenols is mediated by coupled metabolic pathways. Areas covered : The key role of the interplay between drug metabolic enzymes (DMEs) and efflux transporters (ETs), nuclear receptors (NRs), and intestinal microflora in the disposition of polyphenols is summarized. Expert opinion : ETs are shown to act as a 'revolving door', facilitating and/or controlling cellular polyphenol glucuronide/sulfate excretion. Elucidating the mechanisms underlying the glucuronidation/sulfation–transport interplay and structure-activity relationships (SAR) of glucuronide/sulfate efflux by an ET is important. Some new physiologically based pharmacokinetic (PBPK) models could be developed to predict the interplay between glucuronides/sulfates and ETs. Additionally, the combined actions of uridine-5′-diphosphate glucuronosyltransferases, ETs, and intestinal microflora/enterocyte-derived β-glucuronidase enable triple recycling (local, enteric, and enterohepatic recycling), thereby increasing the residence time of polyphenols and their glucuronides in the local intestine and liver. Further studies are necessary to explore these recycling mechanisms and interactions between polyphenols and the intestinal microbiota. Since NRs govern the inducible expression of target genes that encode DMEs and ETs. Determination of the regulation mechanism mediated by NRs using transgenic and knockout animals is still needed.